Arctigenin Exerts Neuroprotective Effect by Ameliorating Cortical Activities in Experimental Autoimmune Encephalomyelitis In Vivo - Wei, Liangpeng; Xue, Zhenyi; Lan, Baihui; Yuan, Shiyang; Li, Yuanyuan; Guo, Cunle; Zhang, Rongxin; Ding, Ran; Shen, Hui (Frontiers in Immunology, 2021)
Multiple sclerosis (MS) is a chronic disease in the central nervous system (CNS), characterized by inflammatory cells invade into the brain and the spinal cord. Among a bulk of different MS models, the most widely used and best understood rodent model is experimental autoimmune encephalomyelitis (EAE). Arctigenin, a botanical extract from Arctium lappa, is reported to exhibit pharmacological properties including anti-inflammation and neuroprotection. However, the effects of Arctigenin on neural activity attacked by inflammation in MS are still unclear. Here we use two-photon calcium imaging to observe the activity of somatosensory cortex neurons in awake EAE mice in vivo and found added hyperactive cells, calcium influx, network connectivity and synchronization, mainly at preclinical stage of EAE model. Besides, more silent cells and decreased calcium influx and reduced network synchronization accompanied by a compensatory rise in functional connectivity are found at the remission stage. Arctigenin treatment not only restricts inordinate individually neural spiking, calcium influx and network activity at preclinical stage, but also restores neuronal activity and communication at remission stage. In addition, we confirm that the frequency of AMPA receptor-mediated spontaneous excitatory postsynaptic current (sEPSC) is also increased at preclinical stage and can be blunted by Arctigenin. These findings suggest that excitotoxicity characterized by calcium influx is involved in EAE at preclinical stage. What’s more, Arctigenin exerts neuroprotective effect by limiting hyperactivity at preclinical stage and ameliorates EAE symptoms, indicating Arctigenin could be a potential therapeutic drug for neuroprotection in MS-related neuropsychological disorders.